2005
DOI: 10.1097/01.mjt.0000144497.85706.e6
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Response to Nilutamide in a Patient with Stage D0.5 Prostate Cancer Who Previously Failed Androgen Deprivation Therapy

Abstract: There is currently no standard therapy for patients with prostate cancer who have progressive rise in PSA levels despite treatment with hormonal ablation and antiandrogen withdrawal (stage D0.5). One potential treatment option is the use of a different androgen receptor antagonist (ARA), such as nilutamide. We report a case of a 66-year-old gentleman with greater than a 46 month sustained response to nilutamide therapy after failing bicalutamide therapy and its subsequent withdrawal. The patient continues to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…This has been previously shown for renal cell carcinoma and hepatocellular carcinoma where the antiangiogenic effects of sorafenib were found to be partly responsible for the potent antitumor activity observed in the clinic (32,33). In the multiple myeloma setting, we found that sorafenib significantly decreased MVD in the bone marrow of multiple myeloma mice and indicating that the antitumoral effects of sorafenib may, at least in part, be mediated by inhibition of angiogenesis.…”
Section: Discussionsupporting
confidence: 81%
“…This has been previously shown for renal cell carcinoma and hepatocellular carcinoma where the antiangiogenic effects of sorafenib were found to be partly responsible for the potent antitumor activity observed in the clinic (32,33). In the multiple myeloma setting, we found that sorafenib significantly decreased MVD in the bone marrow of multiple myeloma mice and indicating that the antitumoral effects of sorafenib may, at least in part, be mediated by inhibition of angiogenesis.…”
Section: Discussionsupporting
confidence: 81%
“…There have been reports supporting the use of nilutamide in bicalutamide-refractory cases. Prolonged response to nilutamide was observed in a patient after failure of bicalutamide therapy and its subsequent withdrawal [15]. There was a high response rate to nilutamide in hormone-resistant prostate cancer that had been exposed to prior antiandrogen therapy including bicalutamide [16].…”
Section: Discussionmentioning
confidence: 99%